(untitled) (Journal of Asian Development Studies, 2023)
The current study reports on the Islamophobic discourses in the print media of Pakistan. Two cases the Khatam-e-Nabuwwat Bill controversy and the Asiya Masih Acquittal case examined to analyze the narratives constructed by the print media in the selected newspapers. The research objectives included exploring the dominant facets and manifestations during the coverage of the religious political party Tehreek-e-Labbaik Pakistan and how the media portrayed the image of TLP and its actors during the sit-in at the Faizabad region of Islamabad. Discourse analysis was employed as a research design, quantitatively studying the editorial and op-ed contents of the newspapers. The coding sheet was designed to collect the data by dividing it into various categories. However, the findings suggest that English dailies were more inclined towards islamophobia topics than Urdu dailies; they were more focused on independent opinion rather than editorial policy. The analysis depicts that the texts used by the media were Islamophobic in nature; we found that metaphors being used in the newspapers at the time of the sit-in conclude that Islamophobic discourses do exist in the print media of Pakistan.